The Benefit of Combining Kinematic Alignment and a Medial Pivot Implant in Total Knee Arthroplasty, The KA–MP Knee: Why and How - Steensen, Robert N. (The Journal of Knee Surgery, 2025)
Kinematic alignment (KA) has emerged as an alternative alignment technique for total knee arthroplasty with the goal of duplicating the pre-arthritic joint surface. Medial pivot (MP) total knee implants duplicate the medial stability of the natural knee and recreate the medial rotational axis of the knee. Each has had favorable results. Combining the two, the KA–MP knee, creates a synergy and achieves better results than KA or MP alone.
Keywords: kinematic alignment; medial pivot; KA–MP knee